Anti-inflammatory effects of ketamine in the treatment-resistant depression: a narrative review - Marta Elżbieta Jóźwiak-Bębenista; Paulina Sokołowska; Edward Kowalczyk; Anna Wiktorowska-Owczarek (Polish Pharmaceutical Society, 2024)
Background: In some depressed patients, especially those not responding to standard antidepressants or with suicidal thoughts or attempts, inflammation as a source of cytokines contributes to a lack of response to the therapies used. An opportunity for such individuals is therapy with ketamine. S-ketamine is a fast-acting antidepressant with high efficacy in treating patients with treatment-resistant depression (TRD). Ketamine is a derivative of phencyclidine, a substance belonging to the group of psychodysleptic agents, also known as hallucinogens. The mechanism of ketamine's antidepressant effect is complex and not yet fully understood. It is thought that it acts mainly by modulating the functioning of the glutamatergic system, which is responsible for the rapid antidepressant effect of ketamine and plays a significant role in the process of neuroplasticity in the course of depression. In recent years, the anti-inflammatory properties of ketamine and its effects on tryptophan metabolism have attracted research interest. Aim of the study: This review aims to discuss and present the current state of knowledge regarding the anti-inflammatory effects of ketamine, which could serve as a crucial component in the effective therapy for depression. This is particularly relevant for the subgroup of patients with TRD who have increased levels of pro-inflammatory cytokines. Materials and methods: The issue was analysed on the basis of a current literature review in both Polish and English languages (published between November 2006 and November 2023) by searching scientific databases: PubMed/Medline and Google Scholar. A search for relevant articles on the anti-inflammatory effects of ketamine was conducted using the keywords: "ketamine" (ketamine), "depression" (depression), treatment-resistant depression (treatment-resistant depression), "inflammation" (inflammation), "kynurenine pathway" (kynurenine pathway), "anti-inflammatory action" (anti-inflammatory action). The described methodology allowed for obtaining reliable information. Results: Preclinical and clinical studies have demonstrated that ketamine appears to induce anti-inflammatory effects, either directly or indirectly (by activating neuroprotective branches of the kynurenine pathway), at least in some patients with TRD. Conclusions: This publication not only expands the current understanding of the mechanism of action of ketamine, but also represents an important addition to the scientific literature in Polish, shedding new light on the complex interactions between the anti-inflammatory and antidepressant effects of this drug.